Synthesis and characterization of poly (2, 5-diyl pyrrole-2-pyrrolyl methine) semiconductor copolymer. (October 2018) - Gherras, Hammou; Yahiaoui, Ahmed; Hachemaoui, Aicha; Belfedal, Abdelkader; Dehbi, Abdelkader; Mourad, Abdel-Hamid I.
Abstract: The proposed technique to synthesise poly {(2, 5-diyl pyrrole) (2-pyrrolyl methine)} (PPPM) copolymer by condensation of pyrrole and pyrrole-2-carboxaldehyde monomers catalyzed by Maghnite-H + is introduced. The protons are exchanged with Maghnite-H +, which is available in the form of a montmorillonite silicate clay sheet. The effect of several parameters such as time and temperature of copolymerization, [pyrrole]/[pyrrole-2-carboxaldehyde] molar ratio, amount of Maghnite-H +, and solvent on the produced poly (2, 5-diyl pyrrole-2-pyrrolyl methine) semiconductor copolymer material (yield%) was investigated. The synthesized PPPM copolymer was characterized using nuclear magnetic resonance, Fourier transform infrared, and ultraviolet–visible spectroscopy. The results show that the synthesized copolymer using the copolymerization technique is a real organic copolymer consisting of two monomers units (i.e, pyrrole and pyrrole-2-carboxaldehyde). Also, the synthesized copolymer is more soluble than polypyrrole in most of the commonly used organic solvents. Hence, copolymerization of pyrrole with pyrrole-2-carboxaldehyde will overcome the insolubility of polypyrrole. In addition, the resultant copolymer exhibits good film formability. The produced copolymer has several potential applications in the field of rechargeable batteries, sensors, capacitors, light emitting diodes, optical displays, and solar cells.